Ekspresi Digital dan Nilai-Nilai Tradisional: Negosiasi Toleransi Beragama Lintas Generasi di Desa Balun - Bettaliyah, Azza; Suyanto, Bagong; Saptyasari, Andria (The Journal of Society and Media, 2025)
This study explores intergenerational communication dynamics in Balun Village, known as the “Pancasila Village” for its religious and cultural diversity. Using a qualitative approach within a cultural studies framework, it examines how harmony is built and maintained between Generation X—bearers of traditional values—and Generation Z—the digitally active generation. Data were collected through in-depth interviews, participant observation, and social media content analysis involving residents of various ages and religions. The findings reveal that intergenerational communication occurs not only verbally but also through actions, cultural participation, and digital symbolization. Generation X transmits harmony through daily practices and lived examples of tolerance, while Generation Z adapts these values through active involvement in youth organizations, interfaith festivals, and online content promoting diversity. Both generations play complementary roles in sustaining social cohesion: Gen X as preservers of local wisdom and Gen Z as mediators who reinterpret harmony in digital spaces. The study concludes that Balun Village’s multicultural harmony is maintained through continuous interaction between local traditions and digital expressions, highlighting intergenerational communication as a vital process for reproducing values, fostering social unity, and strengthening multicultural identity at the community level.